1994
DOI: 10.1056/nejm199412013312206
|View full text |Cite
|
Sign up to set email alerts
|

Variability in Radiologists' Interpretations of Mammograms

Abstract: Although mammography is of value in screening women for breast cancer, radiologists can differ, sometimes substantially, in their interpretations of mammograms and in their recommendations for management. Efforts to improve accuracy and reduce variability in interpretation may increase the effectiveness of mammography in detecting early breast cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
251
1
7

Year Published

1995
1995
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 547 publications
(267 citation statements)
references
References 22 publications
8
251
1
7
Order By: Relevance
“…Therefore, the results closely approximate that expected in actual practice. Secondly, literature has shown that interobserver agreement for the BI-RADS assessment is only fair to moderate (Elmore et al, 1994;Beam et al, 1996;Kerlikowske et al, 1998 ;Redondo et al, 2012 ). To warrant consistent interpreting, the study was designed to exclude the factor of interobserver variation that all breast imaging were interpreted by the same experienced radiologist.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the results closely approximate that expected in actual practice. Secondly, literature has shown that interobserver agreement for the BI-RADS assessment is only fair to moderate (Elmore et al, 1994;Beam et al, 1996;Kerlikowske et al, 1998 ;Redondo et al, 2012 ). To warrant consistent interpreting, the study was designed to exclude the factor of interobserver variation that all breast imaging were interpreted by the same experienced radiologist.…”
Section: Discussionmentioning
confidence: 99%
“…However, for screening mammography, radiologists' experience and annual volume have been studied. In general, radiologist training has been associated with increased performance, [12][13][14][15][16][17] but the literature is conflicting on the relationship between annual volume per radiologist and performance. Our study support findings from five studies showing volume to be of importance.…”
Section: Discussionmentioning
confidence: 99%
“…Radiologist training in general has been associated with increased performance. [12][13][14][15][16][17] Data on the relationship between volume read per radiologist and performance are, however, conflicting, 13,[18][19][20][21][22] whereas associations have been found between some other indicators of radiologists' experience and performance. [23][24][25] However, most studies focused on mammography screening, and no large community based study has evaluated the association between organisational factors and performance of diagnostic mammography.…”
mentioning
confidence: 99%
“…They observed an average intraobserver variability of approximately 8% in addition to a 19% interobserver variability for the diagnosis of cancer, for which the variability in management recommendations was 25%. They also found that 9 out of 10 radiologists recognized fewer than 3% of the mammograms which they screened 5 months prior, while 1 out of 10 claimed to have recognized about 25% of the cases (5). These startling statistics and other discussions on computer-aided diagnosis (CAD) (6)(7)(8) clearly demonstrate the need for (and the possible magnitude of) improvements in the reliability of breast cancer diagnosis.…”
Section: Introductionmentioning
confidence: 96%